IFRS-Based Accounting Policies and Professional Perspectives on the Implementation of Central Bank Digital Currency in Thailand - Thongkul, Teekhatat (Journal of Cultural Analysis and Social Change, 2025)
This study examines how the International Financial Reporting Standards (IFRS) apply to the accounting treatment of Central Bank Digital Currency (CBDC), focusing on Thailand's digital baht. It examines perspectives on recognition, measurement, presentation, and disclosure practices under IFRS by conducting semi-structured interviews with a scholar, five certified public accountants, and a member of the Thailand Federation of Accounting Professions Standards Committee. A thematic analysis using NVivo 14 reveals a consensus regarding the need to revise the current IFRS to better address CBDC concerns. Several informants suggested that digital Thai Baht could be classified as either cash equivalents or financial assets, measured using amortized costs or fair values, and subject to expected credit losses. The disclosure requirements would align with IFRS 7 and IAS 7, emphasizing the need to distinguish between the economic characteristics of digital and traditional currencies. A comprehensive review of the existing IFRS frameworks reveals both conceptual and technical limitations, suggesting the need for more tailored guidance. This study provides valuable information for national and global standard-setting bodies considering future accounting standards specific to CBDCs.